2013
DOI: 10.1177/1471301213511957
|View full text |Cite
|
Sign up to set email alerts
|

People with dementia and carers’ experiences of dementia care and services: Outcomes of a focus group study

Abstract: An ageing population and an associated increase in the prevalence of dementia are of increasing concern in the United Kingdom and worldwide. Recently, the United Kingdom and other European countries implemented national dementia strategies to address this. This paper reports on the outcomes of a focus group study involving people with dementia and carers on their experiences of dementia care and support services in relation to government and third sector agencies' objectives and recommendations. Three focus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 26 publications
6
35
0
Order By: Relevance
“…Experts may focus on these well-known approaches, because realization and implementation of these approaches into practice is still lacking or not satisfactory. Issues in formal dementia care raised by policy and political decision makers agree with previous policy objectives and recommendations and remain highly salient, a finding that has also been highlighted by Sutcliffe and colleagues [ 18 ].…”
Section: Discussionmentioning
confidence: 54%
“…Experts may focus on these well-known approaches, because realization and implementation of these approaches into practice is still lacking or not satisfactory. Issues in formal dementia care raised by policy and political decision makers agree with previous policy objectives and recommendations and remain highly salient, a finding that has also been highlighted by Sutcliffe and colleagues [ 18 ].…”
Section: Discussionmentioning
confidence: 54%
“…At this point, as previously, the participants experienced formal care as being reactive to their needs rather than foreseeing them. Caregivers also experienced insufficient communication and collaboration between professionals in care and services, as also reported in a previous study . At this point, professionals should enable a healthy transition, be proactive and provide tailor‐made care adapted to individual needs in the caring situation.…”
Section: Discussionmentioning
confidence: 79%
“…Sun et al (2007) concluded that rural families use formal services primarily as a result of outreach efforts by professionals, highlighting the need for proactive education strategies and connections to service providers. Lack of knowledge of services is not unique to rural areas, and in fact has been identified in the broader literature as a significant barrier to dementia service provision (Macleod et al, 2017;Phillipson, Jones, & Magee, 2014;Robinson et al, 2009;Sutcliffe, Roe, Jasper, Jolley, & Challis, 2013). Similarly, perceptions of services as inflexible, inappropriate for needs, and not tailored or person-centred are barriers regardless of rurality, as are some of the values and beliefs around caregiving (guilt, reluctance to ask for assistance) and care recipient resistance (Bieber, Nguyen, Meyer, & Stephan, 2019;Boots, Wolfs, Verhey, Kempen, & de Vugt, 2015;Brodaty et al, 2005;Greenwood & Smith, 2015;Macleod et al, 2017;Phillipson & Jones, 2012).…”
Section: Discussionmentioning
confidence: 99%